The legacy of inequality in the status of Turkish and Chinese women’s rights to property - Gümüş, Cansu. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2021., 2021)
This study aims to present an analysis comparing the differences and similarities of women’s property right both as a legal concept and as a practice in China and Turkey. The focus is particularly on property rights because property is a determining factor for women's decision-making power, independence and self determination. In fact, in the reforms Mao and Atatürk made to change the inferior position of women, they gave equality to women in property and inheritance fields. However, many women still cannot freely exercise their right to property and share of inheritance in current Turkey and China. Therefore, in order to understand this contradiction for Turkish and Chinese women who have legally gained rights but could not implement them much in practice, the property rights of women in pre reform period in China and Turkey are examined in detail.
Keywords: Right of property -- China.; Right of property -- Turkey.; Women -- Legal status, laws, etc. -- China.; Women -- Legal status, laws, etc. -- Turkey.